The Relation between Adolescent Depressive Symptoms and Adolescents’ Perceived Attachment to Father and Mother over a Two-Year Period - Vissers, Fleur (Student Undergraduate Research E-journal!, 2017)
This study examined the predictive value of adolescent depressive symptoms on perceived adolescent-mother and adolescent-father attachment two years later, as well as the moderating role of sex. 1110 young adolescents (52,7% boys, Mage = 12.44, SDage = 0.61) were asked to report on their depressive symptoms and perceived at-tachment quality to both mother and father on two waves with a two-year interval. In conclusion, depressive symp-toms are no significant predictor of adolescent-father and adolescent-mother attachment after two years but earlier adolescent-father and adolescent-mother attachment are.